Integration of indigenous knowledge into grade 8 biology teaching and its effect on students’ achievement - Yerukie, Shitaye Kassahun; Ferede, Melaku Wale; Merawi, Tadesse Melese (Journal of Turkish Science Education, 2025)
This study examined the effect of integrating indigenous knowledge on eighth-grade students’ ecology and biodiversity achievement in Injibara, Ethiopia. A nonequivalent pre-test-post-test quasi-experimental research design with a mixed-methods approach was employed. A total of 89 students participated in the study, with two intact classes randomly assigned: 46 students to the control group and 43 to the experimental group. Data were collected using a 25-item Ecology Achievement Test (EAT) and a focus group discussion. The face and content validity of the instruments were confirmed by advisors and subject experts. The internal consistency of the test items was assessed using the Kuder-Richardson formula (KR-20), yielding a coefficient of 0.83. Independent samples t-tests and analysis of covariance (ANCOVA) were used to test the null hypotheses, while means and standard deviations were used to address the research questions. The results showed that the experimental group outperformed the control group in integrating indigenous knowledge. Additionally, the achievement was not significantly influenced by gender, and there was no interaction between gender and the teaching method. These finding suggests that integrating indigenous knowledge into biology instruction enhances students’ academic performance and fosters more effective teaching and learning outcomes.